Reverse transcription of avian sarcoma virus RNA into DNA might involve copying of the tRNA primer. - Taylor, J M (1980)
Some of the double-stranded DNA products from the endogenous reaction of detergent-disrupted virions contain up to 18 3'-terminal nucleotides at a location consistent with their being transcribed from the tRNA primer.